A comparison of proficiency levels in 4-year-old monolingual and trilingual speakers of Afrikaans, isiXhosa and South African English across SES boundaries, using LITMUS-CLT. (1st February 2016) - Perold Potgieter, Anneke; Southwood, Frenette
ABSTRACT: This study investigated how trilinguals fare on the cross-linguistic lexical tasks (CLT)-Afrikaans, -isiXhosa and -South African English (SAE) (cf. Haman et al., 2015) compared to monolingual controls, and whether the CLT-Afrikaans renders comparable results across socioeconomic status (SES) backgrounds. The LITMUS-CLTs were administered to 41 low SES 4-year-olds (11 trilinguals; 10 monolingual speakers of Afrikaans, isiXhosa and SAE) and the LITMUS-CLT-Afrikaans to 11 mid-SES 4-year-old monolinguals. Results (a) indicate that trilinguals' proficiency in their exposure-dominant language did not differ significantly from monolinguals' proficiency, but their proficiency in their additional two languages was significantly lower than monolinguals' proficiency; (b) reflect the extent, but not current amount, of exposure trilinguals had had over time to each of their languages; and (c) show that low and mid-SES monolinguals differed significantly on noun-related, but not verb-related, CLT measures. Possible reasons for and the clinical implications of these results are discussed.